2014
DOI: 10.4161/psb.27700
|View full text |Cite
|
Sign up to set email alerts
|

WRKY transcription factors

Abstract: WRKY transcription factors are one of the largest families of transcriptional regulators found exclusively in plants. They have diverse biological functions in plant disease resistance, abiotic stress responses, nutrient deprivation, senescence, seed and trichome development, embryogenesis, as well as additional developmental and hormone-controlled processes. WRKYs can act as transcriptional activators or repressors, in various homo- and heterodimer combinations. Here we review recent progress on the function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
272
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(278 citation statements)
references
References 144 publications
(256 reference statements)
5
272
0
1
Order By: Relevance
“…The copy number of the WRKY cisacting elements in the upstream region of OsAPx8 (Ascorbate peroxidase 8) gene in the Godawee genome as compared to the reference was significantly high depicting the possible upregulation of OsAPx8 gene expression in Godawee. This is comparable with the previous findings where Hong and Kao [55] showed that the expression of OsAPx8 is enhanced by the accumulation of ABA (Abscisic acid) which in turn enhances the expression of WRKY transcription factors [56]. Additionally, higher numbers of WRKY cisacting elements were also observed in OsMSR2, OsTIR1, OsHKT2;3, OsHKT1;4 and OsSOS1 genes compared to their counterparts in the reference genome.…”
Section: Discussionsupporting
confidence: 90%
“…The copy number of the WRKY cisacting elements in the upstream region of OsAPx8 (Ascorbate peroxidase 8) gene in the Godawee genome as compared to the reference was significantly high depicting the possible upregulation of OsAPx8 gene expression in Godawee. This is comparable with the previous findings where Hong and Kao [55] showed that the expression of OsAPx8 is enhanced by the accumulation of ABA (Abscisic acid) which in turn enhances the expression of WRKY transcription factors [56]. Additionally, higher numbers of WRKY cisacting elements were also observed in OsMSR2, OsTIR1, OsHKT2;3, OsHKT1;4 and OsSOS1 genes compared to their counterparts in the reference genome.…”
Section: Discussionsupporting
confidence: 90%
“…For this, we focused a hot spot QTL region on chromosome 1H (122.17 cM) associated commonly with shoot and root variation which accounted the highest LOD score for Til. In silico analysis of the associated marker BOPA1_7381_1292 with barley Genome Zipper found an essential WRKY transcription factor (WRKY29) gene known for its role in the development of shoot and root (Bakshi and Oelmüller, 2014). Hence, we made full length sequencing of WRKY29 gene in selected genotypes having minor and major QTL alleles for QRdw.1H and QTil.1H.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that MYB4 and MYB12 contain highly conserved W-boxes in their promoters suggests that both might be a target for flg22-induced WRKY TFs as shown in Figure 2. Since WRKYs comprise positive (activating) and negative (repressing) regulators, 35 36 it cannot be predicted in how far the arrangement and location of W-boxes within a given promoter has an impact on binding of positively or negatively acting WRKYs (Imre Somssich, MPIPZ Cologne, personal communication). To evidence this, CHIP-qPCR experiments with anti-all WRKY antibodies should be conducted to prove WRKY binding at the promoters of these two MYB TFs.…”
Section: Resultsmentioning
confidence: 99%